Rivastigmine in apathetic but dementia and depression-free patients with Parkinson's disease: a double-blind, placebo-controlled, randomised clinical trial. Issue 6 (11th November 2013) - Devos, David; Moreau, Caroline; Maltête, David; Lefaucheur, Romain; Kreisler, Alexandre; Eusebio, Alexandre; Defer, Gilles; Ouk, Thavarak; Azulay, Jean-Philippe; Krystkowiak, Pierre; Witjas, Tatiana; Delliaux, Marie; et al.
Abstract : Background: Even with optimal dopaminergic treatments, many patients with Parkinson's disease (PD) are frequently incapacitated by apathy prior to the development of dementia. We sought to establish whether rivastigmine's ability to inhibit acetyl- and butyrylcholinesterases could relieve the symptoms of apathy in dementia-free, non-depressed patients with advanced PD. Methods: We performed a multicentre, parallel, double-blind, placebo-controlled, randomised clinical trial (Protocol ID: 2008-002578-36; clinicaltrials.gov reference: NCT00767091 ) in patients with PD with moderate to severe apathy (despite optimised dopaminergic treatment) and without dementia. Patients from five French university hospitals were randomly assigned 1:1 to rivastigmine (transdermal patch of 9.5 mg/day) or placebo for 6 months. The primary efficacy criterion was the change over time in the Lille Apathy Rating Scale (LARS) score. Finding: 101 consecutive patients were screened, 31 were eligible and 16 and 14 participants were randomised into the rivastigmine and placebo groups, respectively. Compared with placebo, rivastigmine improved the LARS score (from −11.5 (−15/−7) at baseline to −20 (−25/−12) after treatment; F(1, 25) =5.2; p=0.031; adjusted size effect: −0.9). Rivastigmine also improved the caregiver burden and instrumental activities of daily living but failed to improve quality of life. No severe adverse events occurred in the rivastigmine group. Interpretation: Rivastigmine may represent a new therapeutic option for moderate to severe apathy in advanced PD patients with optimised dopaminergic treatment and without depression dementia. These findings require confirmation in a larger clinical trial. Our results also confirmed that the presence of apathy can herald a pre-dementia state in PD. Registration: Clinicaltrials.gov reference: NCT00767091 .